Overweight and obesity may play a role in the pathogenesis of chronic spontaneous urticaria. (1st July 2018) - Zbiciak‐Nylec, M.; Wcisło‐Dziadecka, D.; Kasprzyk, M.; Kulig, A.; Laszczak, J.; Noworyta, M.; Adamus, S.; Brzezińska‐Wcisło, L.; Rogala, B.; Brzoza, Z.
Summary: Background: Chronic spontaneous urticaria (CSU) is one of the commonest diseases in allergological and dermatological practice. It constitutes an interdisciplinary problem, and its pathogenesis is not always easily determined. It has been suggested that metabolic syndrome and hyperlipidaemia are more frequent in patients with CSU, but the influence of overweight and obesity on the development of CSU has not been thoroughly investigated. Aim: To assess the association between body parameters and the development of CSU. Methods: The study enrolled 85 patients with CSU, who were divided into three subgroups: patients whose only symptoms were weals, patients whose only symptom was angio‐oedema, and patients with urticaria and accompanying angio‐oedema. Mean weight, height, body mass index (BMI), body surface area, disease duration and age of disease onset were recorded Results: There was a statistically significant association between CSU and heavier weight, higher BMI, greater affected body surface area and older age at disease onset. Subjects with higher BMI values had a tendency towards longer disease duration. There were no statistically significant differences between the three subgroups. Conclusions: Our results suggest that CSU, especially if of long duration, may be associated with overweight and obesity, while increased body mass can result in later onset of urticaria symptoms. Further analyses to confirm the presented results and possible association between obesity and CSU occurrence are needed.